Periviability Decision-Making: Assessing Provider Characteristics and Cognitive Traits - Ariel Sklar; Amy Yang; Noelle G. Martinez; Lynn M. Yee (Mary Ann Liebert, 2021)
Background: To investigate maternal-fetal medicine (MFM) physicians' approaches to periviable delivery management and examine whether personal characteristics, practice features, or cognitive traits are associated with these approaches. Study Design: This was a cross-sectional survey study of Society for Maternal-Fetal Medicine members. Participants were queried regarding recommendations for periviable delivery management based on eight scenarios, as well as personal/practice characteristics and cognitive traits. Responses to scenarios were summarized as ?willingness to intervene? and ?willingness to recommend termination? scores. We performed a planned sensitivity analysis of the 21-week scenarios, a point considered by some to have clinical equipoise. Top quartile scores were compared with those in the lower three using bivariable and multivariable analyses. Primary analysis assessed association of recommendations with cognitive traits. Secondary analyses included assessment of recommendations with provider personal and practice characteristics. Results: Of 166 respondents, mean age was 45.5 years (?11.4) and 68.7% were female. Willingness to recommend termination was associated with less willingness to consider cerclage for self or loved one (26.7% vs. 69.4%, p?<?0.001) and residence in the West or Northeast (p?=?0.037). Cognitive scores were not associated with recommendations. At 21 weeks, respondents in the top quartile for coping skills were more likely to recommend termination (88% vs. 50%, p?=?0.017), a finding which persisted after controlling for region (adjusted odds ratio 7.3, 95% confidence interval 1.6?33.0). Conclusion: MFM physician recommendations for management of pregnancies at risk of periviable delivery were not associated with provider cognitive traits overall, but did vary by provider personal and practice characteristics. In this small, exploratory study, cognitive traits such as coping skills were associated with recommendations, specifically when counseling women at points of clinical equipoise.